The Treasure of Harageh - Bianchi, Robert Steven.
The present locations of objects distributed by the EEF from Tomb 124 at Harageh are documented with particular attention paid the jewelry and objects of travertine now in the possession of the St. Louis [Missouri] Society of the Archaeological Institute of America.